Exploring industry level capabilities in the U.K. creative industries. Issue 1 (2nd January 2017) - Oliver, John J.
ABSTRACT: The competitive dynamics of the U.K.'s creative industries has changed considerably over the past decade and perhaps none more so than in the publishing industry. There is no doubt that this industry continues to undergo structural changes that compel firms to adapt and transform their business in response to the dynamic nature of competitive environment. Industries have long been examined by researchers from a strategic perspective with various themes of inquiry relating to: industry structure and positioning, industry evolution and development, industry lifecycle, industry change and industry consolidation. This paper argues that 'industry analysis' could usefully draw on Dynamic Capabilities Theory which argues for the strategic adaptation and reconfiguration of firm resources and capabilities in order to address a rapidly changing competitive environment. This paper will present empirical findings from a comparative time-series analysis (1997–2014) of the U.K. publishing industry and compare it to other industries categorised within the U.K.'s creative industries. In doing so, this analysis will add to the limited knowledge base on industry level dynamic capabilities and extend our knowledge on inter-industry comparisons in performance following the reconfiguration of industry resources.